Linking sustainability and spirituality: A preliminary assessment in pursuit of a sustainable and ethically correct world. (20th December 2022) - Leal Filho, Walter; Salvia, Amanda Lange; Ulluwishewa, Rohana; Abubakar, Ismaila Rimi; Mifsud, Mark; LeVasseur, Todd Jared; Correia, Vanderli; Consorte-McCrea, Adriana; Paço, Arminda; Fritzen, Barbara; Ray, Subhasis; Gordon, Neil; et al.
Abstract: The influence of humanity on the environment and the use of natural resources may be affected by spirituality, through awareness for developing a greater conscience about the implications of human actions and needs to adjust these in achieving sustainable development. However, the literature indicates a lack of consensus about operationalizing spirituality outside the management field and its connection with sustainability. This study focused on the relation between these topics in the educational sector and investigated whether spirituality informs the teaching and research of sustainability within higher education curricula. An online survey was administered to a convenience sample (n = 100) of academic staff working at higher education institutions in 25 countries. The questions posed by the research instrument included open-ended and multiple-choice queries, that yielded qualitative and quantitative data. Overall, the results suggest that there is widespread awareness about making connections between spirituality and sustainability and a general agreement about the usefulness of including spiritual aspects in sustainability teaching and research practices. However, there are some elements which hinder progress in this area, such as a common understanding of spirituality definition and an apparent lack of training to handle matters related to spirituality as part of teaching and research. The study presents actions to promote a better integration of sustainability and spirituality, which include a greater emphasis on matters related to sustainability, human well-being, and ethics, a part of initiatives on spirituality, and involvement of key stakeholders. Graphical abstract: Image 1